Comparison of patient radiation exposure in coronary angiography via the trans-radial versus trans-femoral approach - Venkatesh Gurajala; Charishma Daruru; Kumar Narayanan; L. Sridhar (Indian Heart Journal)
Background: Cardiac catheterization via the trans-radial approach (TRA) has shown several advantages over the trans-femoral approach (TFA) but with a concern of higher radiation exposure. Considering the growing experience with TRA, this study compares patient's radiation during coronary angiography using TRA versus TFA. Methods: This study included consecutive patients undergoing coronary angiogram over a year at tertiary hospital performed by experienced operators through radial or femoral access. Parameters compared between the two routes included fluoroscopy time (FT), cineangiography time (CT), cini-sequences (CS), and patient radiation exposure quantified by Air Kerma (AK) and Dose Area Product (DAP). Results: A total of 910 patients were studied, with 461 (50.6 %) undergoing coronary angiography (CAG) via TFA and 449 (49.4 %) via TRA. The mean age was similar between the femoral (54.07) and radial groups (53.7) years (p = 0.33), with slightly lesser proportion of males in the femoral group (74.62 % vs 79.73 %; p = 0.06). The mean (SD) DAP and AK were 15.71 (7.05) Gy·cm2 and 258.3 (99.9) mGy for the femoral group, compared to 20.76 (9.48) Gy·cm2 and 352.2 (151.5) mGy for the radial group (both p < 0.001). The mean (SD) FT, CT, and CS were 1.32 (0.94) minutes, 40.4 (9) seconds, and 5.93 (1.22) for the femoral group, compared to 2.19 (1.67) minutes, 44 (10) seconds, and 6.17 (1.26) for the radial group (all p < 0.01). Conclusion: Coronary angiography via TRA is associated with increased patient's radiation. Future studies should investigate strategies to reduce radiation exposure in trans-radial procedures.